Kemijske analizne metode v kmetijstvu in toksične snovi v ekosistemih: Navodila za laboratorijske vaje - Kristl, Janja (University of Maribor Press, 2022)
Chemical Analytical Methods in Agriculture and Toxic Compounds in Ecosystems: Instructions for Laboratory Exercises. Instructions for laboratory exercises support some of the content of the lectures in Chemical Analytical Methods in Agriculture and Ecotoxicology. They help students understand some terms (extraction, atomic absorption spectrometry, molecular absorption spectrometry, liquid chromatography, acid digestion) and laboratory procedures. The manual describes the procedures for sample preparation and quantitative determination of sodium chloride, proteins, total phenols, sugars, oxalates, hydrocyanic acid in food samples, and sulfur dioxide in wine. The qualitative determination of nitrate and nitrite in food extracts and qualitative tests for the detection of natural and synthetic pigments are also included. The content also includes the determination of plant-available copper and the water-soluble and bioavailable lead fraction in soil samples.